Enhancement of noise immunityand increase in data transmission speed in telemetrical communication system - Zhuikov, Valery; Tereschenko, Tetiana; Yamnenko, Yulia; Khokhlov, Yuriy (Publishing House of Lviv Polytechnic National University, 2015)
Effective monitoring of physiological parameters indicating the state of a human being under extremal conditions is highly important in order to provide fast and efficient medical care in acute cases. Thus, development of biotelemetry technologies is a matter of topical interest. The paper is concerned with the methods of enhancement of noise immunity and increase in data transmission speed in a telemetry communication system on the basis of a new discrete spectral transform in an oriented basis. The proposed idea consists in using matched filters with the transient characteristics coinciding with the basis functions of the proposed spectral transform in an oriented basis. This new approach allows enhancing of noise immunity and reducing of computational complexity in comparison with widely known methods. Ефективний контроль за фізіологічними параметрами стану людини в екстремальних умовах є надзвичайно актуальним. Важливим кроком на шляху підвищення швидкості надання медичної допомоги та реагування на загрозу здоров’ю людини є впровадження технології біотелеметрії. Стаття присвячена методам підвищення завадостійкості та швидкості передавання даних телеметрії в системі зв'язку на базі розробленого авторами нового математичного апарату – дискретного спектрального перетворення в орієнтованому базисі. Запропонована авторами ідея полягає у використанні узгоджених фільтрів з перехідними характеристиками, які збігаються з базисними функціями цього перетворення. Впровадження технології передавання даних на базі перетворення в орієнтованому базисі підвищує завадостійкість та зменшує трудомісткість алгоритмів, що її реалізують, у порівнянні з широковідомими аналогічними методами.
Підвищення завадостійкості та швидкості передавання даних в телеметричній комунікаційній системі
Keywords: biotelemetry technologies; noise immunity; data transmission; telemetry communication system; spectral transform